(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
The luminescent material K3La0.8Eu0.2(PO4)2 has been prepared by solid state reaction at 950ºС with overage grain size 20–100 μm. The peculiarities of pure binary phosphate and lanthanum orthophosphate formation in molten system of K-Lа-P-Mo-O have been studied. For binary sections KРO3-K2Mo2O7, KРO3-K2Mo3O10 and K4Р2O7-K2MoO4 the acid-base equilibrium has been studied as a key factor for the phase formation control. The crystallization area of K3La(PO4)2 is found for the most basic melts, while di- and trimolybdate melts tend to LaPO4 formation. The purity of single phases is checked by FTIR spectroscopy and X -Ray powder diffraction. The compound K3La(PO4)2 crystallizes in monoclinic system, space group Р21/m, a= 9,632(1) Å, b=5,66(1) Å, c=7,514(1) Å β=90,55(1)° V=409,62(2) Å3. Due to a structural peculiarity of lanthanum polyhedra to be isolated from each other by phosphate groups the latter compound has been used as a host for doping with Eu3+ luminescent center. The incorporation of the emitting center into K3La(PO4)2 host is more likely to be realized by isovalent way. Their emission spectra consist of a well-known set of peaks which are associated with radiation transitions from excited 5D0 level on 7FJ (J = 0-4) manifold levels of the ground state of the Eu3+ ion, showing the strongest emission lines in a region 590–625 nm. The emission spectra do not depend on excitation wavelength. The integral intensity corresponding to 5D0→7F2 and 5D0→7F1 bands shows equal redistribution of emission in orange-red region.